(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine effectiveness of PGE2 vaginal tablet for induction of labour in prolonged pregnancy. Study Design: Interventional (Quasi Experimental) Place and Duration of Study: Study was carried out in department of Obstetrics and Gynaecology, Sir Ganga Ram Hospital, Lahore from March 2009 to July, 2010 Material and Method: Sixty pregnant ladies at 41 weeks of gestation with alive fetuses visiting the antenatal clinic who met the inclusion criteria were enrolled in the study. These patients were admitted and after detailed history and examination, relevant investigations were carried out. Admission CTG, pelvic assessment and bishop scoring was done in all the patients and Proforma was filled up. Induction of labour with PGE2 vaginaI tablet started in patients with Bishop score < 5. All the patients were observed for onset of labour if no labour pains started then PGE2 vaginal tablet was repeated at 6 hours interval and maximum 3 tablets were used, each at Interval of 6 hrs. If labour pains started then progress of labour was monitored. In all the patients success of induction, number of PGE2 vaginal tablets used, need of syntocinon for augmentation of labour, mode of delivery, indications of caesarean section (C-section), Apgar score of the baby, and side effects of PGE2 vaginal tablet were recorded. Results: Induction of labour with PGE2 vaginal tablet in patients with Bishop score < 5 was successful in 54(90%) patients and failed in 6(10%) patients. Out of 54 patients, who had successful induction 48(88.9%) patients had vaginal delivery while 6(11.1%) patients had emergency C-section. In 20(33%) patients, 3 tablets of PGE2 were used. Out of which 6 patients had failed induction so emergency LSCS done. While in 10(17%) patients, 2 tablets of PGE2 were required for initiation of labour and 30(50%) patients went in labour by use of only a single tablet of PGE2. Out of 48 patients, who delivered vaginally only 20(41.7%) patients required syntocinon while 28(58.3%) patients did not require augmentation of labour. Apgar score at 1 minute was less than 8 in 15(25%) babies while 45(75%) babies had Apgar score more than 8 and Apgar score at 5 minutes was more than 8 in 59(98.3%) newborns and was less than 8 only in one (1.7%) baby. Hypertonic uterine contractions developed in 1(1.7%) patient resulting in fetal distress, nausea and vomiting occurred in 1(1.7%) patient. Conclusion: Prostaglandin is effective and safe method for induction of labour in patients with poor Bishop score and side effects are minimum.